A potential intellectual property issue with the way in which some nomenclature code decisions are made. (21st June 2022) - Maxwell, Stephen J.; Underdown, Michael
Abstract: This article examines the legal status of nomenclature codes and their application to denomination in certain forms of intellectual property, in particular plant breeder's rights and patents for micro‐organisms. Its objective is to show how rigidity and the absence of appeals against nomenclature decisions can have adverse effects on the rights and even earning potential of applicants.